Literacy: The missing link in boko haram insurgency (2019)
In spite of the efforts of governments and international organisations infighting insurgents and insurgencies as exemplified by the Boko Haram war in Nigeria, there are some missing links. Efforts like recruiting armed officers and expending money to buy arms and ammunitions are but mere acts; to fight insurgency there is the need to institute a proper and workable process. This process which has been practiced in many instances with sustainable results is called a literacy process. Without this process, insurgents will continue to be with Nigeria as a country, Africa as a continent and the whole world as an entity. This paper therefore identifies a literacy process for fighting insurgency and suggests ways of achieving a peaceful multi-ethnic society like Nigeria